مدى إمكانية الإدارة الالكترونية القضاء على الفساد الإداري في الجزائر؟ - زوقاغ نادية (جامعة المسيلة محمد بوضياف, 2019)
إنّ الثورة المعلوماتية التي يشهدها العالم في الوقت الحالي؛ قد أثرت على مختلف مجالات الحياة، حيث أصبحت تقنية المعلومات والاتصالات تستعمل وتستغل في نشاطات وتصرفات الأفراد (كعقود التجارة الإلكترونية)، وحتى في التصرفات والعقود التي تبرمها الدول بمختلف أجهزتها (العقود الدولية عن بعد). الملاحظ أنّ الجزائر كانت متأخرة في تبنيها للتجارة الإلكترونية، حيث لم تصدر قانون التجارة الإلكترونية إلا في السنة الجارية (2018)، وهذا عكس الدول الأجنبية وحتى العربية، التي انتشرت فيها التجارة الإلكترونية بصفة كبيرة، وهو ما أدى بهذه الدول إلى التفكير في استغلال تقنية المعلومات والاتصالات في المعاملات الإدارية، وذلك للاستفادة من مزايا هذه التقنية خدمة للمواطنين، وتسهيلا للعمل الإداري من جهة، كما تلعب هذه التقنية دور فعال في مكافحة ظاهرة الفساد الإداري من جهة أخرى. فأصبحت معظم الدول تستعمل الوسائل الإلكترونية لممارسة العمل الإداري المنوط بها، وهو ما يعرف بـ: "الإدارة الإلكترونية". إنّ نجاح الإدارة الإلكترونية في مكافحة الفساد الإداري؛ مرهون بمدى توفر مقومات هذه الإدارة الحديثة كخطوة أولى، ثم معرفة الأساليب والطرق الفعّالة لهذه الآلية لمكافحة الفساد الإداري، وهو ما سنحاول توضيحه في هذه الورقة البحثية. Abstract: Actually, the information revolution that the world is currently witnessing has affected various aspects of life. Where, the information and communication technique is used and exploited in different activities and behaviors of individuals too (such as electronic trade contracts), and even in the behaviors and the contracts which are concluded by countries with various organs (International contracts). Notice that, Algeria was late in its adoption of electronic trade. The e-trade law was not issued until this year (2018). In the contrary of foreign and even Arab countries, in which electronic trade has been widely widespread. This situation has led these countries to think about the exploitation of information and communications technique in administrative transactions, in order to take profit from this technique to serve citizens and to facilitate administrative tasks on one side. This technique also plays an effective role in fighting the phenomenon of administrative corruption on the other side. Most of these countries use electronic means to practice the administrative tasks assigned to them, which is known as “electronic administrative”. The success of the electronic administration in fighting administrative corruption depends on the availability of the elements of this modern administration as a first step, then knowing the methods and effective processes of this mechanism to fight administrative corruption. This is what we will try to explain in this article.
Keywords: الفساد الإداري، الإدارة الالكترونية، المعلوماتية، وسائل الاتصال الحديثة، الخدمة العمومية